PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SDN 004 SAMARINDA ULU TAHUN AJARAN 2024/2025 - Desmita, Helma; Dwiyono, Yudo; Sukriadi; Wahyuningsih, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of the use of Wordwall learning media on the learning outcomes of Pancasila Education students in grade IV of SD Negeri 004 Samarinda Ulu. The background of this research is the low learning outcomes of students in the subject of Pancasila Education where the learning outcomes of class IV A students are below the Learning Objective Skill Criteria (KKTP) of 70, students who score below KKTP reach 67%. and the lack of use of interactive and fun learning media in the classroom. The research was carried out in the odd semester of the 2024/2025 school year. This type of research is quantitative with a Pre-Experimental approach using a one group pretest-posttest design. This research was carried out at SD Negeri 004 Samarinda Ulu, Samarinda City. The population in this study is all grade IV students, and the research sample was taken by purposive sampling, namely 28 students in grades IV-A. The instrument used was a multiple-choice test to measure learning outcomes before and after treatment. The results of the study showed that there was a significant difference between the pretest and posttest scores where the average pretest score was 42.81 and the average posttest score was 67.33. The hypothesis test using a paired sample t-test yielded a significance value of 0.000, indicating that Ha was accepted and H0 was rejected. This indicates that Wordwall media has succeeded in improving students' understanding of the concept of angles better than conventional learning methods. This research is expected to contribute to the development of learning media that is more effective and relevant to the needs of students